MANTEGNA TAROCHI IN CLINICAL SETTING: SEBUAH STUDI LITERATUR PENGGUNAAN TAROT DI DALAM ASESMEN PSIKOLOGIS - Putra, Rangga Wirianto (Prosiding PESAT, 2015)
This literature study aims to look more closely what if the Tarot cards are used as an assessment tool in transpersonal psychology. In this case, the Tarot cards used are Mantegna Tarocchi - E-series made in Italy in the year 1465. The study of literature discusses the origins of Tarot more comprehensively to do with the Transpersonal Psychology approach, where Transpersonal Psychology approach is basically see humans based body, mind / mental, soul and spirit. This literature study using historical studies, psychology, and philosophy in particular hermeneutic philosophy. Results of the study of literature shows that it is possible if the Tarot is used in the assessment of psychological, especially with the approach of Transpersonal Psychology as T arot load relationship or the principle of synchronicity between someone with a row of Tarot cards.